The Impact of The Zimbabwe Government's Fiscal Policy on The Destruction of The Country's Economy - Kudzai, Tonderai (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This political economy study in international relations explains the impact of the government's fiscal policy on foreign loans to the IMF in 2020. The fiscal policy carried out by the Robert Mugabe government has negatively impacted Zimbabwe's economy. The land reform policy was carried out to forcibly take land belonging to white farmers and give it to supporters of Robert Mugabe's political party. The land reform policy reduced economic growth and experienced hyperinflation, and as a result, the IMF suspended aid for Zimbabwe's foreign loans. This study aims to explain the impact of land reform policies on IMF foreign loans in 2020 and describe their impact on the Zimbabwean economy. The object of this research is land reform policies in Zimbabwe. This qualitative research uses descriptive methods and collects data from books, journals, official publications, and relevant websites. This paper uses a behavioralist perspective and the theory of international economic cooperation by Anne Kruenger, Deepak Lal. The results showed that hyperinflation in Zimbabwe was terrible for society, and the IMF decided to make economic aid to Zimbabwe worse.